Changing paradigms in the management of diverticulitis. (September 2016) - Horesh, Nir; Wasserberg, Nir; Zbar, Andrew P.; Gravetz, Aviad; Berger, Yaniv; Gutman, Mordechai; Rosin, Danny; Zmora, Oded
Abstract: The management of diverticular disease has evolved in the last few decades from a structured therapeutic approach including operative management in almost all cases to a variety of medical and surgical approaches leading to a more individualized strategy. There is an ongoing debate among surgeons about the surgical management of diverticular disease, questioning not only the surgical procedure of choice, but also about who should be operated and the timing of surgery, both in complicated and uncomplicated diverticular disease. This article reviews the current treatment of diverticulitis, with a focus on the indications and methods of surgery in both the emergency and elective settings. Further investigation with good clinical data is needed for the establishment of clear guidelines. Highlights: This review outlines the most significant changes that diverticular disease management in recent years. The review gives physicians an updated view on the most current studies in treatment for acute diverticulitis. The review focus on the surgical management and the indications for surgery in diverticulitis.